2009
DOI: 10.1177/1352458508101320
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial to investigate the effects of functional electrical stimulation and therapeutic exercise on walking performance for people with multiple sclerosis

Abstract: Exercise may provide a greater training effect on walking speed and endurance than FES for people with SPMS. FES may provide an orthotic benefit when outcome is measured using the same parameters. More research is required to investigate the combined therapeutic effects of FES and exercise for this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
86
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 22 publications
(46 reference statements)
3
86
1
Order By: Relevance
“…This may have included patients who did not achieve any ankle dorsiflexion weeks (9%). 4 A significant orthotic effect has also been found in a long-term observational study that included a progressive group of 32 people with MS and familial spastic paraplegia. 5 Researchers found a significant improvement in orthotic effect after 3 months of using FES (7%), which was still significant after 11 months (4%).…”
Section: Participantsmentioning
confidence: 83%
See 1 more Smart Citation
“…This may have included patients who did not achieve any ankle dorsiflexion weeks (9%). 4 A significant orthotic effect has also been found in a long-term observational study that included a progressive group of 32 people with MS and familial spastic paraplegia. 5 Researchers found a significant improvement in orthotic effect after 3 months of using FES (7%), which was still significant after 11 months (4%).…”
Section: Participantsmentioning
confidence: 83%
“…The existence of an orthotic effect through using FES over a short period is well established. [3][4][5][6] In an initial case series that included 23 people with MS, researchers found a 16% increase in walking speed after 4.5 months of using FES. 3 The findings from the case series were further supported by a two-group randomized controlled trial (N = 44) in which a significant improvement in orthotic effect was found after 12 weeks (6%).…”
mentioning
confidence: 99%
“…28 The duration of each session ranged from 15 minutes 32,36 to 24 hours. 27 The sample size (per group) ranged from 9 29 to 36 31 participants. The mean age of the groups ranged from 38 34 to 57 [26][27][28] years.…”
Section: Electrical Stimulation Interventionsmentioning
confidence: 99%
“…27 The sample size (per group) ranged from 9 29 to 36 31 participants. The mean age of the groups ranged from 38 34 to 57 [26][27][28] years. Participants were mostly females (range, 30%-84%) with RRMS and minimal to severe disability as measured using the EDSS.…”
Section: Electrical Stimulation Interventionsmentioning
confidence: 99%
See 1 more Smart Citation